Blind SELEX approach identifies RNA aptamers that regulate EMT and inhibit metastasis. - Yoon,S; Armstrong,B; Habib,N; Rossi,JJ (Molecular Cancer Research, 2017)
Identifying targets that are exposed on the plasma membrane of tumor cells, but expressed internally in normal cells, is a fundamental issue for improving the specificity and efficacy of anticancer therpeutics. Using blind cell Systemic Evolution of Ligands by EXponetial enrichment (SELEX), which is untargeted SELEX, we have identified an aptamer, P15, which specifically bound to the human pancreatic adenocarcinoma cells. To identify the aptamer binding plasma membrane protein, liquid chromatography tandem mass spectrometry (LC-MS/MS) was used. The results of this unbiased proteomic mass spectrometry approach identified the target of P15 as the intermediate filament vimentin, biomarker of epithelial–mesenchymal transition (EMT), which is an intracellular protein but is specifically expressed on the plasma membrane of cancer cells. As EMT plays a pivotal role to transit cancer cells to invasive cells, tumor cell metastasis assays were performed in vitro. P15-treated pancreatic cancer cells showed the significant inhibition of tumor metastasis. To investigate the downstream effects of P15, EMT-related gene expression analysis was performed to identify differently expressed genes (DEG). Among five DEGs, P15-treated cells showed the downregulated expression of matrix metallopeptidase 3 (MMP3), which is involved in cancer invasion. These results, for the first time, demonstrate that P15 binding to cell surface vimentin inhibits the tumor cell invasion and is associated with reduced MMP3 expression. Thus, suggesting that P15 has potential as an anti-metastatic therapy in pancreatic cancer.